A New Perspective for Future Precipitation Change from Intense Extratropical Cyclones. Issue 21 (13th November 2019) - Kodama, C.; Stevens, B.; Mauritsen, T.; Seiki, T.; Satoh, M.
Abstract: Extratropical cyclones, major contributors to precipitation in the midlatitudes, comprise mesoscale fronts and fine‐scale convective storms. Intense oceanic cyclones pose natural hazards, making reliable projections of their changes with global warming of great interest. Here, we analyze the first ever global climate simulations to resolve such mesoscale dynamics of extratropical cyclones. The present‐day structure, frequency, and precipitation of the oceanic extratropical cyclones compare well with reanalyses and new satellite datasets that resolve the multiscale cloud‐precipitation system. Simulated precipitation from intense oceanic cyclones increases at a rate of 7%/K 1, following Clausius‐Clapeyron, with warming. The same scaling is apparent also in the interhemispheric contrast, suggesting that the latter could serve as a predictor of the former. Projected changes in precipitation from intense oceanic cyclones with warming may thus be testable using a reliable global observation network of precipitation in the present day. Plain Language Summary: Precipitation in midlatitudes is strongly governed by extratropical cyclones. Its future change is of great societal concern for adaptation to a warmer world. In this study, we use a new kind of global model and a new satellite dataset to resolve fine‐scale and frontal features of cyclones and their changes with warming. The simulation shows that the amount of precipitation around the intense oceanic cyclones will increase due to global warming, and furthermore, the rate of precipitation change around the intense oceanic cyclones is closely related to the precipitation contrast between the northern and southern hemispheres in the present climate. This suggests that the future precipitation change associated with intense oceanic cyclones could be inferred from the difference between the northern and southern hemispheres in the present climate. Key Points: The first global climate simulations to explicitly represent the mesoscale dynamics of extratropical cyclones are analyzed Precipitation from intense cyclones scales with temperatures across hemispheres and with global warming following Clausius‐Clapeyron Projected change in precipitation from intense cyclones may thus be testable using global observations of precipitation in the present day